TINJAUAN REGULASI PELAYANAN PUBLIK BIDANG ADMINISTRASI DESA KECAMATAN SUNGAI TEBELIAN KABUPATEN SINTANG - Martinus Syamsudin (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2019)
The study in this study is the Review of Public Service Regulation in the Village Administration in Sungai Tebelian Subdistrict, Sintang District, the purpose of the research is to know and analyze the Public Services in the Village Administration field. The research method uses descriptive qualitative research. The results of this study indicate that the Village Administration Public Service Procedure has been carried out and the recording has been carried out from the recording books and has been owned and can be implemented. The Quality of Village Administration Services has been carried out based on the implementation of basic tasks and functions as well as work monitoring to suit what is needed by the community. The Operational Procedure of Village Administration Services in serving the community has been carried out as well as the Principles of Service in the Administration of Village Administration aspects of simplicity, clarity and certainty, the time of completion, Security, Justice and Timeliness of the village apparatus in accordance with indicators of good public service. Keywords: Regulation, Services, Administration